Reducing violent student behavior through culturally based counseling: Mediation analysis of the fairness - DYP Sugiharto; M Mulawarman; S Sunawan; Ashari Mahfud; M Muslikah; Thrisia Febriyanti; Ujang Khiyarusholeh; Nailu Rohmatika (KONSELOR, 2023)
This study investigates the impact of Iso Trimorogo counseling, a culture-based counseling approach rooted in Tri Dharma Mangkunegaran Philosophy, on reducing violent behavior in high school students by fostering the character trait of fairness. The research involved 120 high school students from Central Java Province, Indonesia divided into an experimental group receiving Iso Trimorogo counseling and a control group subjected to conventional counseling methods. The efficacy of the counseling was assessed using a fairness character scale and a bullying behavior scale, administered pre- and post-treatment. The study employed bootstrapping analysis with 5000 resampling iterations, maintaining an error threshold of 5% (p < 0.005). The results indicated a significant direct effect of Iso Trimorogo counseling in diminishing violent behavior (F = 9.027) and an indirect effect through the mediation of fairness character development (F = 4.026), with a negative correlation between fairness character and violent behavior (R = 0.389). These findings underscore the importance of integrating character education, particularly focusing on fairness, in counseling strategies to effectively address violent behavior in schools. The study advocates for the adoption of culture-based counseling approaches like Iso Trimorogo in educational settings to enhance student behavior and character development.